Private equity investment committee paper: Varta as an attractive investment opportunity in the battery industry - Fonseca, Madalena de Lima Mayer Branquinho da (2022)
This work was performed by a group of 4 members of Nova School of Business and Economics’ Master in Finance. The purpose is to develop an Investment Committee Paper (ICP) of VARTAAG, in which the main goal is to evaluate the company ́s attractiveness for a leverage buy out. VARTA is a German battery manufacturing company that operates globally through two high-growth business segments, offering a wide portfolio of batteries suitable for many different applications. The choice of VARTA was a result of a combination of attractive factors, such as ,the low debt levels and stable Cash Flows, its global presence and leadership positioning in most of it send markets its competitive edge and the future growth prospects. Both the company and the respective market were analyzed in order to evaluate the firm ́s positioning, financial performance and its ability to capture the current and future market trends within the battery industry and all its end markets. Based on such analysis, we defined the most suitable investment strategies, focusing in maximizing the firm ́s value creation and to potentiate a solid exit and attractive returns after the 5 year holding period.